Preparation of potassium sodium niobate in tellurite glass system doped with Er2O3 - Ploypailin Yongsiri (2018)
In the present study, potassium sodium niobate (KNN) doped with Er2O3in TeO2glasses were successfully prepared using melting-quenching method. The glass composition of 70KNN-30TeO2 mol% doped with 1 mol% of Er2O3has been chosen. A batch was subsequently melted at 800°C and 900°C for 30-60 min and heated at the temperature ranging between 300-530°C in order to form the glass ceramics with desired crystal phases. XRD results showed that KNN crystals distributed over the glass-ceramic samples. From SEM observation, it was found that nano-crystals of several phases were precipitated in all glass-ceramic matrices. Dielectric constant increased with increasing heat treatment temperature. © 2014 Taylor and Francis Group, LLC.